2014
DOI: 10.1371/journal.pone.0086373
|View full text |Cite
|
Sign up to set email alerts
|

Endocytosis of Fgf8 Is a Double-Stage Process and Regulates Spreading and Signaling

Abstract: Tightly controlled concentration gradients of morphogens provide positional information and thus regulate tissue differentiation and morphogenesis in multicellular organisms. However, how such morphogenetic fields are formed and maintained remains debated. Here we show that fibroblast growth factor 8 (Fgf8) morphogen gradients in zebrafish embryos are established and maintained by two essential mechanisms. Firstly, Fgf8 is taken up into the cell by clathrin-mediated endocytosis. The speed of the uptake rate de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 61 publications
0
7
0
Order By: Relevance
“…These results indicate that KIT-containing early endosomes can indeed transit KIT signals to the downstream molecules as a signaling endosome. A very recent study showed that Bafilomycin A1, which inhibits protein transport from early to late endosome, enhanced FGF (fibroblast growth factor)-induced activation of ERK1/2 in HEK293 cells [27] . However, in contrast to Akt, we didn’t observe the enhanced phosphprylation of ERK1/2 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that KIT-containing early endosomes can indeed transit KIT signals to the downstream molecules as a signaling endosome. A very recent study showed that Bafilomycin A1, which inhibits protein transport from early to late endosome, enhanced FGF (fibroblast growth factor)-induced activation of ERK1/2 in HEK293 cells [27] . However, in contrast to Akt, we didn’t observe the enhanced phosphprylation of ERK1/2 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…(Rocky Hill, NJ). Imatinib mesylate (STI571) purchased from Selleck (Houston, TX) was used to inhibit KIT activity and Bafilomycin A1 purchased from Sigma Aldrich (St. Louis, MO) was used to inhibit the protein transport from early to late endosome [27] .…”
Section: Methodsmentioning
confidence: 99%
“…For fluorescence analysis in zebrafish, the following plasmids were used: xWnt5a (16), zf Fz7-CFP (36), xRor2-mCherry, xWnt5a-GFP (37), mem-mCherry, and GFP-GPI (38). For immunohistochemistry of DMZ explants, Xenopus embryos were injected into the dorsal equatorial zone at the four-cell stage, and DMZ explants were dissected from gastrula embryos at stage 10.…”
Section: Methodsmentioning
confidence: 99%
“…The strength of FGF8 signal in the mesoderm is controlled by a double-step process of endocytosis. 46 , 49 The signaling strength of FGF8 in mesodermal cells is dependent on the rate of this endocytosis. In the first step, an invagination in the cell membrane occurs around the activated FGF8–FGFR1 complex.…”
Section: Epidemiologymentioning
confidence: 99%